Evaluation of the Effects of Different Natural Dietary Feed Additives on Performance and Intestinal Histomorphology in Quails - Yesilbag, D; Abdullahoglu, E; Urkmez, E; Acar, A; Asmaz, D; Kara, M (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of the present study was to investigate the influence of a commercial probiotic and a commercial essential oil blend and their mixture, as a natural feed additive, on growth parameters live weight (LW), live weight gain (LWG), feed intake (FI), feed conversion ratio (FCR), carcass yield (CY) and small intestinal histomorphology of quails. A total of 200 1-day-old Japanese (Coturnix coturnix japonica) quails, including both males and females, were divided into four groups containing 50 quails and treated as follows: (1) a control treatment without medication (2) 18 g ton-1 probiotic; (3) 300 g ton-1 essential oil blend and (4) 18 g ton-1 probiotic plus 300 g ton-1 essential oil blend. The results of the research show that the additives added to quail diets do not have a significant effect (P > 0.05) on the performance parameters of LW, LWG, FI and FCR. However, significant differences (P < 0.05) were found in the CY, which is one of the performance parameters. A probiotic addition of 18 g ton -1 (treatment 1) to the quail diet resulted in a significant increase (P < 0.05) in carcass yield. Moreover, the addition of natural feed additives such as probiotics, essential oil blends and mixture to quail diets caused significant (P < 0.001) increases in villus heights and crypt depth in the duodenum and ileum segments. In addition, significant (P < 0.05) enlargements were found in the villus surface area in the experimental groups compared to the control group. In conclusion, in this study, it was determined that the addition of feed additives, which are developed as an alternative to antibiotics to the quail diet did not have a negative effect on performance and caused significant differences in the effective parameters in the evaluation of intestinal health.